Fitness professionals' guide to sport nutrition and weight management - Kruskall, Laura J. Ph.D., R.D., CSSD (California Healthy Learning, 2010)
Fitness Professionals' Guide to Sports Nutrition and Weight Management is designed to be a resource for fitness professionals who want to better understand the basic factors involved in sound nutrition. The first part of the book explains what constitutes credible information on nutrition and details where fitness professionals can find such information. The book also defines an acceptable scope of practice for fitness professionals concerning nutrition and explains how giving sound nutritional advice can differ from practicing as a dietitian. In that regard, dietary guidelines and information that are appropriate for fitness professionals to share with their clients are covered in a step-by-step manner. In addition, the book explores the various energy systems that power the body and examines the basic of digestion. The factors that affect digestion, as well as the primary role of each organ involved in the process, are discussed. A detailed loot at each of the various essential nutrients is also included. The second part of the book looks at the impact of energy balance on weight management. The components of energy expenditure and how they can be collectively assessed are discussed, as are the essential points of concern about body composition. This part of the book also reviews the basic principles of sound weight management and explains what does and what does not constitute a sound strategy for loosing weight. The final chapter in this part discusses disordered eating, including the role that a fitness professional can play in helping someone who suffers from an eating disorder. The third part of the book features answers to a series of commonly asked questions concerning sports nutrition and weight management. Each response, framed with the appropriate scope of practice for fitness professionals, is based on the most up-to-date information available. The focus of this part of the book is helping fitness professionals who want to clarify or better understand the nutrition-related issues that are relevant to their clients.
Chapter 1: The fitness profession and credible nutrition information -- Chapter 2: Dietary guidelines that fitness professionals can use -- Chapter 3: Energy systems -- Chapter 4: Digestion basics -- Chapter 5: Carbohydrates -- Chapter 6: Lipids -- Chapter 7: Protein -- Chapter 8: Vitamins and minerals -- Chapter 9: Fluid and electrolyte needs -- Chapter 10: Energy balance -- Chapter 11: Body composition -- Chapter 12: Weight-loss strategies -- Chapter 13: Disordered eating
Includes bibliographical references
Keywords: Athletes -- Nutrition